Design and Evaluation of Fast Disintegrating Tablets of Metformin by Effervescence Method - Sahu, Ravi Kiran (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT: The objective of the present study was to develop simple fast disintegrating tablets of Metformin for improving patient compliance, especially paediatric and geriatric categories by effervescent method. Croscarmellose sodium was used as superdisintigrant along with blend of sodium bicarbonate, tartaric acid and anhydrous citric acid in different ratios as effervescent material and directly compressible mannitol to enhance the mouth feel. The prepared batches of tablets were evaluated for weight variation, friability, hardness, drug content uniformity, in-vitro dispersion time. The tablet formulation containing 10% w/w of Crospovidone, 20% w/w sodium bicarbonate, 15%w/w citric acid and 20%w/w of MCC emerged as the overall best formulation (with an in vitro dispersion time of approximately 18s, t50%=1.23 min and t70%=1.57 min), based on the in-vitro drug release characteristics, compared to commercial conventional tablet formulation (which shows 118s, 14.09 min and 23.48 min respectively). Infrared spectroscopic studies revealed no drug–excipient interactions. Short-term stability studies conducted at 40 ±2°C/75±5%RH on the best formulation indicated that there were no significant changes in drug content. The present study clearly demonstrates that fast dissolving tablets of Metformin could be successfully prepared by direct compression method in a cost effective manner.